P-282 Aquaporin-3 Mediates Hydrogen Peroxide Dependent Responses to Environmental Stress in Colonic Epithelia. (February 2017) - Thiagarajah, Jay; Chang, Jeffrey; Goettel, Jeremy; Lencer, Wayne
Abstract : Background: The colonic epithelium forms the first cellular barrier between the complex microbial milieu of the colonic lumen and the body. How the epithelium senses and responds to this environment is critical to protecting the body and controlling inflammation. Hydrogen peroxide (H2 O2 ) is an important signaling molecule in cells and is involved in epithelial repair and host defense. Studies have shown that patients with early-onset inflammatory bowel disease have impaired regulation of H2 O2 . Extracellular H2 O2 is produced by cell-membrane oxidases (e.g., NADPH oxidase 1 [NOX1]), secreted oxidase enzymes, and commensal bacteria within the gut. However, the mechanism(s) by which H2 O2 in the intestinal environment signals to the epithelium of the intestine is poorly understood. Aquaporin 3 (AQP3), one of the aquaporin family of plasma membrane channels, is known to conduct H2 O2 and is highly expressed in the colonic epithelium. Here we investigated whether AQP3-dependent H2 O2 transport plays a role in the epithelial response to wounding and in the response to pathogenic infection. Methods: H2 O2 transport was assessed dynamically using H2 O2 -sensitive fluorescent probes in human colonic epithelial cells, and murine AQP3 +/+ and AQP3 −/− colonic crypts and enteroids. Wound repair was assessed by a scratch wounding assay in vitro and biopsy-induced injury in vivo. Wound-associated epithelial cell lamellipodia and focal adhesion formation was assessed by immunocytochemistry and immunoblot. AQP3 +/+ and AQP3 −/− mice were infected with the colonic pathogen C. rodentium and bodyweight, epithelial cytokine expression, histology, and bacterial clearance assessed. In some experiments AQP3 +/+ mice were administered the anti-oxidant n-acetyl cysteine (NAC). Results: We show that signal transduction by H2 O2 depends upon entry into the cell by transit through AQP3. In response to injury, AQP3-depleted colonic epithelial cells showed defective lamellipodia, focal adhesions, and repair after wounding, and a defective H2 O2 response after exposure to the intestinal pathogen C. rodentium. Correspondingly, AQP3 −/− mice showed impaired healing of superficial wounds in the colon, and impaired mucosal innate immune responses against C. rodentium infection, manifest by reduced crypt hyperplasia, reduced epithelial expression of IL-6 and TNF-alpha, and impaired bacterial clearance. Treatment of AQP3 +/+ mice with the anti-oxidant NAC after C. rodentium infection resulted in phenotypically similar changes in epithelial responses to AQP3 −/− mice. Conclusions: These results explain the mechanism for signaling by extracellular H2 O2 in the colonic epithelium, and implicate AQP3 in innate immunity and inflammation at mucosal surfaces. Further studies will define the mechanisms and signaling pathways by which AQP3-mediated H2 O2 transport alters colonic epithelial function. Modulation of AQP3-mediated H2 O2 signaling pathways may provide new therapeutic targets for treatment of intestinal inflammatory disorders.